The Singularity of the German Doctorate as a Signal for Managerial Talent: Causes, Consequences and Future Developments - Egon Franck; Christian Opitz (Management Revue, 2007)
The paper focuses on signaling options for managerial talent under different higher education regimes. The educational paths in a sample of top managers of the 100 largest publicly traded companies in the U.S., France and Germany are consistent with our theoretical conjectures. For the singular role of the German doctorate, the traditional chair system in doctoral education and training is essential. The effects of higher education reforms are discussed. In Germany the doctorate is a powerful signal for managerial talent. Future signaling options are closely tied to German higher education reform.
Keywords: 650; doctoral education; signaling; managerial talent; German higher education; higher education reform